Pan-cancer analysis of CTNNB1 with potential as a therapeutic target for human tumorigenesis - Mandana AmeliMojarad; Melika AmeliMojarad; Xiaonan Cui; Parvin shariati (Informatics in Medicine Unlocked, 2023)
Background: Despite the different studies on the oncogenic role of Catenin Beta 1 (CTNNB1) and its association with cancer pathogenesis, there is no pan-cancer study to clarify its oncogenic role in tumorigenesis and cancer development. Methods: By using Cancer Genome Atlas (TCGA), and The Genotype Tissue Expression (GTEx), and cbioportal databases we evaluated the expression of CTNNB1 in all 33 cancer types. Furthermore, CTNNB1 phosphorylation and methylation pattern were assessed using the UALCAN portal. In addition, survival analysis, tumor-immune infiltration, CTNNB1 molecular mechanisms, and gene enrichment analysis were carried out using different bioinformatic tools and databases. Results: Our findings indicate the overall increase of CTNNB1 levels in most cancers, associated with the worst patient outcome and prognosis. CTNNB1 seems to affect tumor immune infiltration by mediating tumor-infiltrating lymphocytes and cancer-associated fibroblast. Also, enrichment analysis indicated that CTNNB1 is related to different cellular signaling process such as Wnt and Hippo signaling pathways. Conclusion: Collectively, CTNNB1 is a pivotal oncogene with the capability to be considered as an ideal biomarker and therapeutic target in different cancers.